Towards Autonomous Robotic Systems 16th Annual Conference, TAROS 2015, Liverpool, UK, September 8-10, 2015, Proceedings - Dixon, Clare; Tuyls, Karl.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 16th Annual Conference on Towards Autonomous Robotics, TAROS 2015, held in Liverpool UK, in September 2015. The 16 revised full papers presented together with 18 short papers were carefully reviewed and selected from 59 submissions. The overall program covers various aspects of robotics, including navigation, planning, sensing and perception, flying and swarm robots, ethics, humanoid robotics, human-robot interaction, and social robotics.
Keywords: Computer science; Computers; Data mining; User interfaces (Computer systems).; Artificial intelligence; Image processing; Computer Science; Artificial Intelligence (incl. Robotics).; Image Processing and Computer Vision; User Interfaces and Human Computer Interaction; Data Mining and Knowledge Discovery; Computation by Abstract Devices; Information Systems Applications (incl. Internet).; Electronic books